Determining Intravenous Complications in Patients with Infusion Pumps - Zehra Gök-metin; Leyla Özdemir (Hemşirelikte Araştırma Geliştirme Derneği, 2016)
Objective: Intravenous infusion complications are placing patients at high risk and creating an economic burden for hospitals and health institutions. Available infusion pumps provide to decrease complications and patient safety. However, life-threatening complications may occur in patients with infusion pumps. This study was performed to determine of incidence of intravenous complications and influencing factors in patients with infusion pumps. Method: The study utilized causal model comparison and cross sectional design and was carried out with 120 patients monitored with infusion pump in a single university hospital in Turkey. Independent variables such as patients' demographic data, catheter type, catheter site, intravenous infusion type, infusion duration, and total infusion volume in patients with infusion pump that influencing complications were investigated in this study. Results: Intravenous infusion complications developed in 10% of patients in present study. Thrombophlebitis 6.7% was the most frequent complication. The study did not reveal any significant difference between the patient's age, gender, number of comorbidities and incidence of intravenous infusion complications p>0.05 . Statistically significant differences were found between the catheter site, infusion duration, total infusion volume and incidence of intravenous infusion complications p